KONSELING KELUARGA: SEBUAH DINAMIKA DALAM MENJALANI KEHIDUPAN BERKELUARGA DAN UPAYA PENYELESAIAN MASALAH - Ahmad Syarqawi (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
The presence of family counseling brings a sense of happiness to some people. The existence of family counseling at this time has carried its fragrant name so famous in every country. In its implementation in the field, family counseling has contributed a lot in solving family problems, both mild and severe problems. Therefore, the author will contribute ideas to the appreciation of the development of family counseling increasingly needed presence. the discussion of this journal will be directed to a main idea about family counseling services and supported by various theories and results of previous research.Keywords: family life, family dynamics, settlement